The Anachronistic Disaster of the Electoral College - Durdag, Sofia (Maine Policy Review, 2021)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. The essay prompt for 2021 asked students to offer their opinions on whether the Electoral College has outlived its usefulness, or if it is more important than ever given the country’s current deep political polarization. This is the first-place essay.
Keywords: electoral college